2016
DOI: 10.1016/j.envres.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular identification of Legionella spp. isolated from water and surrounding air samples in Italian healthcare facilities

Abstract: The application of the SBT method allowed to verify the homology among Legionella strains from water samples and the surrounding air. The results showed that the same Lpn strains were present in the air and water samples, and a new Legionella strain was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…The model showed a statistically significant effect of laboratories between membrane filters (p < 0.0001) and for interactions (p < 0.0001), as shown in Table 2. 5,6 <0.0001…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model showed a statistically significant effect of laboratories between membrane filters (p < 0.0001) and for interactions (p < 0.0001), as shown in Table 2. 5,6 <0.0001…”
Section: Resultsmentioning
confidence: 99%
“…Legionnaires' disease (LD) is a severe and potentially lethal pneumonia caused by the inhalation of aerosolized water from natural and artificial water systems contaminated with Legionella [1][2][3][4][5][6][7][8][9]. The disease may be community-acquired or nosocomial and can occur as both sporadic and epidemic cases.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 of 13 (8%) samples of drinkable water (gushing fountain) was positive, but it has not yet been shown that Legionella is transmitted by ingestion of contaminated water. It is also true that to drink from the gushing fountains, they must be approach by the face which means inhaling droplets that could potentially be contaminated [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, due to the evidence of Legionella presence even in the aerosol, in very recent years we have associate the control of this latter to the routine water control (data not yet published). Indeed, many recent studies suggest and recommend the concurrent research water/air to increase the probability of finding the microorganism [41][42][43]. This aspects are important not only in order to plan the management and monitoring actions of the pipelines, but also in view of a Public Health approach, with the specific aim of preventing illnesses in the exposed population.…”
Section: Discussionmentioning
confidence: 99%